Risk factors for central hypoventilation in anti-N-methyl-D-aspartate receptor encephalitis - Zou, Xuan; Jing, Xi-yue; Zhou, Guan-en (Frontiers in Immunology, 2025)
ObjectiveThis study aims to identify the risk factors for central hypoventilation in patients with anti-N-methyl-D-aspartate receptor (anti-NMDAR) encephalitis.MethodsPatients with anti-NMDAR encephalitis who were hospitalized between January 2020 and January 2025 were identified from the Tianjin Huanhu Hospital database, affiliated with Tianjin University. Patients were categorized into a central hypoventilation group and a non-central hypoventilation group, and potential risk factors were collected. Statistical methods were used to compare the two groups and identify risk factors.ResultsThe analysis revealed that the central hypoventilation group exhibited a higher incidence of involuntary movements (χ²=5.662, P=0.017), lower admission Glasgow Coma Scale (GCS) scores (Z=-3.749, P<0.001), and higher cerebrospinal fluid (CSF) antibody titers compared with the non-hypoventilation group (Z=-3.344, P=0.001). Multivariate logistic regression analysis identified only admission GCS score and CSF antibody titer as independent risk factors. A lower GCS score [P=0.018; OR (95% CI): 0.556 (0.343, 0.903)] and a higher CSF antibody titer [P=0.048; OR (95% CI): <0.001 (0.000, 0.903)] significantly increased the likelihood of central hypoventilation.ConclusionDisturbances in consciousness and elevated CSF antibody titers are risk factors for central hypoventilation in patients with anti-NMDAR encephalitis. It is imperative to closely monitor the respiratory status and oxygenation levels of patients identified as high-risk, conduct regular blood gas analyses, and implement respiratory support and more aggressive immunotherapy when necessary.